Elongation Factor Thermo Unstable (EF-Tu) Moonlights as an Adhesin on the Surface of Mycoplasma hyopneumoniae by Binding to Fibronectin - Yu, Yanfei; Wang, Hongen; Wang, Jia; Feng, Zhixin; Wu, Meng; Liu, Beibei; Xin, Jiuqing; Xiong, Qiyan; Liu, Maojun; Shao, Guoqing (Frontiers in Microbiology, 2018)
Mycoplasma hyopneumoniae is a colonizing respiratory pathogen that can cause great economic losses to the pig industry worldwide. Although putative virulence factors have been reported, the pathogenesis of this species remains unclear. Here, we used the virulent M. hyopneumoniae strain 168 to infect swine tracheal epithelial cells (STEC) to identify the infection-associated factors by two-dimensional electrophoresis (2-DE). Whole proteins of M. hyopneumoniae were obtained and compared with samples cultured in broth. Six differentially expressed proteins with an increase in abundance of ≥1.5 in the cell infection group were successfully identified. A String network of virulence-associated proteins showed that all the six differential abundance proteins were involved in virulence of M. hyopneumoniae. One of the most important upregulated hubs in this network, elongation factor thermo unstable (EF-Tu), which showed a relatively higher expression in M. hyopneumoniae-infected STEC and obtained a higher score on mass spectrometry was successfully recombined. In addition to its canonical enzymatic activities in protein synthesis, EF-Tu was also reported to be located on the cell surface as an important adhesin in many other pathogens. The cell surface location of EF-Tu was then observed in M. hyopneumoniae with flow cytometry. Recombinant EF-Tu (rEF-Tu) was found to be able to adhere to STEC and anti-rEF-Tu antibody enclosed M. hyopneumoniae decreased adherence to STEC. In addition, surface plasmon resonance (SPR) analysis showed that rEF-Tu could bind to fibronectin with a specific and moderately strong interaction, a dissociation constant (KD) of 605 nM. Furthermore, the block of fibronectin in STEC also decreased the binding of M. hyopneumoniae to the cell surface. Collectively, these data imply EF-Tu as an important adhesin of M. hyopneumoniae and fibronectin as an indispensable receptor on STEC. The binding between EF-Tu with fibronectin contributes to the adhesion of M. hyopneumoniae to STEC.